2016
DOI: 10.5935/abc.20160020
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Pulmonary Vascular Resistance by Magnetic Resonance in Systolic Heart Failure

Abstract: BackgroundPulmonary hypertension is associated with poor prognosis in heart failure. However, non-invasive diagnosis is still challenging in clinical practice.ObjectiveWe sought to assess the prognostic utility of non-invasive estimation of pulmonary vascular resistances (PVR) by cardiovascular magnetic resonance to predict adverse cardiovascular outcomes in heart failure with reduced ejection fraction (HFrEF).MethodsProspective registry of patients with left ventricular ejection fraction (LVEF) < 40% and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is accepted that the combination of raised pulmonary pressures and RV dysfunction suggests that the contractile reserve is struggling to maintain output against an increased afterload, and, indeed, previous studies have shown that it entails a poor prognosis. 3133 The finding of a PVR >5 WU in patients with heart failure and reduced LVEF, quantified by the same method 15 we used, was recently associated with an increased risk of adverse events at nine months of follow-up. 33…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It is accepted that the combination of raised pulmonary pressures and RV dysfunction suggests that the contractile reserve is struggling to maintain output against an increased afterload, and, indeed, previous studies have shown that it entails a poor prognosis. 3133 The finding of a PVR >5 WU in patients with heart failure and reduced LVEF, quantified by the same method 15 we used, was recently associated with an increased risk of adverse events at nine months of follow-up. 33…”
Section: Discussionmentioning
confidence: 97%
“…3133 The finding of a PVR >5 WU in patients with heart failure and reduced LVEF, quantified by the same method 15 we used, was recently associated with an increased risk of adverse events at nine months of follow-up. 33…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The CMR-derived model was estimated as: pulmonary vascular resistance [in Wood units (WUs)] = 19.38 – [4.62 × Ln pulmonary artery average velocity (in cm/s)] – [0.08 × RV ejection fraction (in %)] ( 24 ). This CMR method to noninvasively estimate pulmonary vascular resistance has been used in patients with PH and also in patients with heart failure and reduced LV ejection fraction (EF), in whom pulmonary vascular resistance > 5 WU was associated with an increased risk of adverse events at 9 months follow-up ( 38 , 39 ). Based on all this, we believe that this CMR method could also be integrated in the global evaluation of the RV in the setting of FTR in order to better understand if the RV contractile reserve is struggling to maintain output against an increased afterload, a finding which, indeed, previous studies have shown that entails a poor prognosis ( 39 ).…”
Section: Diagnosticsmentioning
confidence: 99%